2007
DOI: 10.1590/s0066-782x2007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Pré-condicionamento isquêmico e monitorização da função medular na abordagem da aorta torácica descendente

Abstract: SummaryObjectives: To evaluate the effectiveness of acute ischemic preconditioning (IP), based on somatosensory evoked potentials (SSEP) monitoring, as a method of spinal cord protection and to asses SSEP importance in spinal cord neuromonitoring.Methods: Twenty-eight dogs were submitted to spinal cord ischemic injury attained by descending thoracic aorta cross-clamping. In the C45 group, the aortic cross-clamping time was 45 min (n=7); in the IP45 group, the dogs were submitted to IP before the aortic cross-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…SEP monitoring has been reported to be a useful and non-invasive method for protecting spinal cord function and detecting spinal cord ischemic injury ( 24 ). SEPs have been used frequently because they may be recorded intraoperatively under general anesthesia ( 25 ). However, SEPs primarily examine the sensory pathway of the dorsal column, and the specificity and sensitivity of SEPs for monitoring the motor neuron pathways has been questioned ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…SEP monitoring has been reported to be a useful and non-invasive method for protecting spinal cord function and detecting spinal cord ischemic injury ( 24 ). SEPs have been used frequently because they may be recorded intraoperatively under general anesthesia ( 25 ). However, SEPs primarily examine the sensory pathway of the dorsal column, and the specificity and sensitivity of SEPs for monitoring the motor neuron pathways has been questioned ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spinal cord monitoring is a well-documented mechanism for detecting intraoperative spinal cord injury. It has also been suggested that ischemic preconditioning of the spinal cord before EVAR may be protective against neurological injury [12]. ACS is a well-documented complication of these procedures [2,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have indicated that ischemic preconditioning has protective actions in many organs (Zheng and Zuo, 2004; Wakeno-Takahashi et al ., 2005; Mônaco et al ., 2007). However, ischemic preconditioning is impractical for clinical practice (Tong et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%